Pulmonary micro‐tumor emboli resulting in paradoxical emboli: a case report. (1st February 2018) - Morin‐Thibault, Louis‐Vincent; Wiseman, Daniel; Fortin, Michelle; Couture, Christian; Provencher, Steeve
Abstract : Pulmonary tumor embolism (PTE) is a rare manifestation of cancer. It is characterized by the presence of tumor cell emboli in the pulmonary arterioles and capillaries leading to an elevation of pulmonary vascular resistance. The ante‐mortem diagnosis is difficult. We report a case of PTE associated with recurrent breast cancer that presented with neurological symptoms due to paradoxical cerebral embolism.